2018
DOI: 10.4081/gh.2018.707
|View full text |Cite
|
Sign up to set email alerts
|

Air versus water temperature of aquatic habitats in Delhi: Implications for transmission dynamics of Aedes aegypti

Abstract: The present study was planned to characterize the microclimate experienced by Aedes larvae in different breeding habitats by determining the temperature variations in water kept in containers during different months under natural conditions. The study was conducted in three municipal zones of Delhi. In each site, four types of container material (plastic, cement, iron and ceramic) were chosen for recording the water temperature in the containers. Daily air and water temperatures (mean, maximum and minimum valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…For instance, it has been shown that the average diurnal water temperature in plastic containers can reach up to 35.6 ºC, exceeding the thermal optima range of 15–35 ºC for the development of Ae. aegypti immatures [ 56 , 57 ]. This suggests that plastic containers may become unsuitable larval sites depending on their daily amount of sunlight exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown that the average diurnal water temperature in plastic containers can reach up to 35.6 ºC, exceeding the thermal optima range of 15–35 ºC for the development of Ae. aegypti immatures [ 56 , 57 ]. This suggests that plastic containers may become unsuitable larval sites depending on their daily amount of sunlight exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The range of temperatures represented the full range at which each species can persist when reared individually, including temperatures at which both species are found in the field (Brady et al 2014, Sinka et al 2020). For example, in Delhi, where both species are found, temperatures of mosquito larval habitat range from 14.3° to 36.1°C, depending on the habitat type (Kumar et al 2018). The strain of Ae.…”
Section: Methodsmentioning
confidence: 99%
“…As the species breeds in small containers (Stefopoulou et al, 2018), the water temperature can quickly reach high values, even if the air temperature is lower (Kumar et al, 2018). During spring, the temperature conditions often allow a complete development from egg to adult in 2-3 weeks; however, clear field information on the mean duration of a generation time is still missing.…”
Section: Articlementioning
confidence: 99%